2014
DOI: 10.14411/eje.2014.022
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of plant extracts on growth, development and α-amylase activity in the red flour beetle Tribolium castaneum (Coleoptera: Tenebrionidae)

Abstract: abstract. The bioinsecticidal effects of methanolic extracts of the leaves of castor bean, Ricinus communis, and papaya, Carica papaya, on the red flour beetle, Tribolium castaneum, were studied. More specifically, larval weight, larval mortality, percentage pupation, percentage adult emergence and F1 progeny production were recorded. We also studied the effects of the extracts on α-amylase activity and amylase gene expression in T. castaneum. The extracts of R. communis and C. papaya, which were administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Determining the inhibitory abilities of exogenous compounds on the activities of enzymes in the insect body is an important method for evaluating insecticidal activities ( Li et al. 2007 , Tatun et al. 2014a ,b).…”
Section: Discussionmentioning
confidence: 99%
“…Determining the inhibitory abilities of exogenous compounds on the activities of enzymes in the insect body is an important method for evaluating insecticidal activities ( Li et al. 2007 , Tatun et al. 2014a ,b).…”
Section: Discussionmentioning
confidence: 99%
“…Plant based compounds, being natural and organic, may provide the starting point for such discoveries. In these regards, recent studies have identified several promising natural extracts of plant exhibiting insecticidal activities in stored grain systems (Tatun et al, 2014, Tripathi et al, 2009). Such botanical extracts may have various modes of action and can help in pest management by repelling the pest away, may act as feeding and oviposition deterrent, and at the same time may act as insecticides (Mohan and Fields, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This enzyme converts complex carbohydrates into oligosaccharides, which are hydrolyzed to glucose by α-glucosidases (Terra et al, 1996). The changes in α-amylase activity are related to the feeding behaviour and development in T. castaneum (Tatun et al, 2014). In addition, changes in α-amylase activity are associated with different types of plant diets in Helicoverpa armigera (Kotkar et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Higher doses induce pupation and adult emergence, but caused deformities in the pupae and adults and a reduction in α-amylase activity. It is reported that changes in amylase gene expression and α-amylase activity in T. castaneum (Tc-Amy) correlate well with developmental profi le, with a high expression of amylase in the larval stage, a very low level in pupae and the highest activity in adults, with in the latter it is about 2-fold higher than that in larval stage (Tatun et al, 2014). Thus, further investigations are needed to reveal the relationship between Tc-Amy and ecdysteroid in the red fl our beetle.…”
Section: Discussionmentioning
confidence: 99%